An evaluation of knowledge, attitude and practice of Indian pharmacists towards adverse drug reaction reporting: A pilot study - Akram Ahmad; Isha Patel; Rajesh Balkrishnan; G P Mohanta; P K Manna (Perspectives in Clinical Research, 2013)
Background: Pharmacovigilance is a useful to assure the safety of medicines and protect consumers from their harmful effects. Healthcare professionals should consider Adverse Drug Reaction (ADR) reporting as part of their professional obligation and participate in the existent pharmacovigilance programs in their countries. In India, the National PV Program was re-launched in July 2010. Objectives: This survey was conducted in order to assess the knowledge, attitude and practice of Indian pharmacists with the aim of exploring the pharmacists′ participation in ADR reporting system, identifying the reasons of under reporting and determining the steps that could be adopted to increase reporting rates. Materials and Methods: A cross-sectional survey was carried out among the pharmacists in India using a pretested questionnaire with 33 questions (10 questions on knowledge, 6 on attitude, 7 on practice, 7 on future of ADR reporting in India and 3 on benefits of reporting ADRs.). The study was conducted, over a period of 3 months from May 2012 to July 2012. Results: Out of the 600 participants to whom the survey was administered, a total of 400 were filled. The response rate of the survey was 67%. 95% responders were knowledgeable about ADRs. 90% participants had a positive attitude towards making ADRs reporting mandatory for practicing pharmacists. 87.5% participants were interested in participating in the National Pharmacovigilance program, in India. 47.5% respondents had observed ADRs in their practice, and 37% had reported it to the national pharmacovigilance center. 92% pharmacists believed reporting ADRs immensely helped in providing quality care to patients. Conclusion : The Indian pharmacists have poor knowledge, attitude, and practice (KAP) towards ADR reporting and pharmacovigilance. Pharmacists with higher qualifications such as the pharmacists with a PharmD have better KAP. With additional training on Pharmacovigilance, the Indian Pharmacists working in different sectors can become part of ADR reporting system.